Scarless gene disruption enabled by a dual-plasmid knockout platform in a clinical infant-derived Bifidobacterium breve strain - Gao, Zhenxuan; Feng, Lihui (Frontiers in Microbiology, 2025)
In the developing gut of infants, Bifidobacteria establish themselves and become one of the predominant microbial populations, playing vital roles in host health by modulating immune responses, inhibiting the growth of pathogenic bacteria, and enhancing nutrient metabolism. While Bifidobacterium strains from Western populations have been extensively studied, those derived from Chinese infants remain underexplored. Given the substantial impact of geography, diet, and host genetics on gut microbiota composition and function, strains from the Chinese population may possess unique probiotic properties with significant scientific and clinical relevance. In this study, we isolated a highly abundant clinical Bifidobacterium breve strain with intrinsically high transformation efficiency from the feces of a healthy Chinese infant. We obtained its complete genome using Oxford Nanopore sequencing. To assess its genetic tractability, we first employed two conventional double-crossover gene knockout strategies. A pyrE mutant was successfully constructed using a shuttle vector, leveraging its 5-fluoroorotic acid (5-FOA) sensitivity as a counterselection marker. To enable efficient, scarless genome editing, we developed a novel dual-plasmid system that markedly improved the selection of single-crossover events. This approach enabled robust and flexible genetic manipulation of a clinically derived B. breve strain that was previously recalcitrant to standard knockout techniques. Our work not only provides a powerful platform for dissecting the probiotic mechanisms of B. breve, but also serves as a valuable reference for the development of genetic tools applicable to other clinically relevant strains.